THE EFFECT OF YOU TUBE CHANNEL ANIA AND ELSIA ON SECOND LANGUAGE ACQUISITION IN EARLY CHILDREN - WURIY HANDAYANI; ZAINAL RAFLI; ENDRY BOERISWATI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
In line with technological developments, English learning media can be done through You Tube. You Tube developed into You Tube Kids to cater to children consumers. You Tube Kids provides various interesting channels in English such as Peppa Pig, Coco Melon and Ania-Elsia. An interesting phenomenon was found in a child who is able to speak English because he often watches Ania and Elsia's You Tube channels. In their daily habits, the child uses Indonesian as the first language and English as the second language. This study tries to reveal the influence of You Tube Kids on second language acquisition. The study of first and second language acquisition material is in the field of psycholinguistics studies. The research method used is a qualitative research method using case study research. From this research, You Tube Kids is very influential in the acquisition of a second language in terms of cognitive, vocabulary and pronunciation of words well.